Improving Early Literacy Through Kamishibai Storytelling: Action Research in an Indonesian Kindergarten - Simatupang, Nurhenti Dorlina; Sholichah, Sefy Amaliatus; Simanjuntak, Irena Agatha (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
This study investigates the effectiveness of the Kamishibai storytelling method in improving early childhood literacy skills among children aged 5–6 years. A classroom action research design was employed, consisting of two cycles conducted at TK Aisyiyah 16 Surabaya. Cycle I was implemented from February 12–13, 2024, and Cycle II from February 19–20, 2024. Each cycle followed the four core stages of action research: planning, action, observation, and reflection. The research involved 15 children from Group B1 and utilized participatory observation as the primary data collection technique. Data were analyzed using descriptive statistical methods based on literacy performance indicators, including the ability to appreciate reading, respond to story content, recognize narrative elements, and retell stories. The results demonstrated a substantial improvement in children's literacy development following the application of the Kamishibai method. In Cycle I, 13% of participants were categorized as Beginning, 47% as Achieving, and 20% as Exceeding. By Cycle II, no children remained in the Beginning category, while 66.67% were categorized as Achieving and 33.33% as Exceeding. These outcomes indicate that the Kamishibai method—when applied with appropriate storytelling techniques such as expressive voice, visual cues, and interactive engagement—can significantly enhance children's reading interest, comprehension, and narrative skills. The study contributes to the field of early childhood education by emphasizing the role of expressive, visual-based storytelling in fostering foundational literacy. However, limitations include the small sample size and single-site design, which restrict generalizability. Future research should explore the long-term impacts of Kamishibai through longitudinal and mixed-method studies in diverse educational settings. The findings support the potential of Kamishibai as an engaging and inclusive literacy strategy that integrates narrative structure with multimodal learning to support early language development.